2013
DOI: 10.1002/jpln.201200643
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning of carbon and nitrogen during decomposition of 13C15N‐labeled beech and ash leaf litter

Abstract: The aim of this study was to determine the influence of leaf‐litter type (i.e., European beech—Fagus sylvatica L. and European ash—Fraxinus excelsior L.) and leaf‐litter mixture on the partitioning of leaf‐litter C and N between the O horizon, the topsoil, the soil microbial biomass, and the CO2 emission during decomposition. In a mature beech stand of Hainich National Park, Thuringia, Germany, undisturbed soil cores (∅︁ 24 cm) were transferred to plastic cylinders and the original leaf litter was either repla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 48 publications
2
9
0
Order By: Relevance
“…This is supported by the result that the recovery of ash root litter-derived C in C MB is higher than of beech root litter-derived C. No differences were observed in the recovery of root litter-derived C compared to leaf litter-derived C within one species. Further, in agreement with a field decomposition experiment on beech and ash leaf litter (Langenbruch et al, 2014), no differences were observed in the recovery of litter-C in PL-beech leaf and PL-ash leaf , and no mixture effects were observed on the incorporation of ash and beech litter C into MB. The measured recovery of litter C in C MB is an average of all microbial functional groups, as CFE estimates the total MB (Vance et al, 1987;, irrespective of its activity (Bailey et al, 2002).…”
Section: Microbial Biomasssupporting
confidence: 88%
See 1 more Smart Citation
“…This is supported by the result that the recovery of ash root litter-derived C in C MB is higher than of beech root litter-derived C. No differences were observed in the recovery of root litter-derived C compared to leaf litter-derived C within one species. Further, in agreement with a field decomposition experiment on beech and ash leaf litter (Langenbruch et al, 2014), no differences were observed in the recovery of litter-C in PL-beech leaf and PL-ash leaf , and no mixture effects were observed on the incorporation of ash and beech litter C into MB. The measured recovery of litter C in C MB is an average of all microbial functional groups, as CFE estimates the total MB (Vance et al, 1987;, irrespective of its activity (Bailey et al, 2002).…”
Section: Microbial Biomasssupporting
confidence: 88%
“…Mixture of ash and beech leaf litter led to enhanced mineralization of ash leaf litter but did not affect beech leaf litter mineralization, which agrees with findings of a decomposition experiment in a beech stand (Langenbruch et al, 2014). Several studies found synergistic mixture effects on the decomposition of leaf litter from various tree species, but there also exist studies that found purely additive effects on leaf litter decomposition (H€ attenschwiler et al, 2005).…”
Section: Effects Of Litter Mixturesupporting
confidence: 50%
“…The soil texture in 0–10 cm was characterized as 3% sand, 82% silt and 15% clay [33] . According to Zanella et al [35] , the forest floor was classified as a dysmull (OL + OF) to hemimoder (OL + OF + discontinuous OH) covering a topsoil (0–5 cm) with pH KCl of 3.3 [36] .…”
Section: Methodsmentioning
confidence: 99%
“…For the experiment, we used leaf litter from European ash ( Fraxinus excelsior L.) and European beech ( Fagus sylvatica L.). Labeled leaf litter was produced in a closed greenhouse with 13 CO 2 -enriched atmosphere (∼300 ‰ V-PDB) for one growing season [36] . As reference litter (unlabeled treatments), leaf litter of beech and ash were collected in the Hainich National Park.…”
Section: Methodsmentioning
confidence: 99%
“…Biomass enriched in 15 N can be produced by application of labelled fertilizers ( Weatherall et al 2006 , Langenbruch et al 2013 ), foliar sprays ( Zeller et al 1998 ) or by direct injections into the plant vascular system ( Swanston and Myrold 1998 ). This latter methodology is potentially most efficient as the valuable 15 N-labelled material is not lost via misting ( Bowden et al 1989 ), exposed to soil sinks ( Nadelhoffer et al 1999 b ) or exported from the immediate area by soil hydrology.…”
Section: Introductionmentioning
confidence: 99%